Carnosine-enriched functional food enhances micro- and macrovascular endothelium-independent vasodilation in competitive athletes - a randomized study - Peric, L.; Drenjancevic, I.; Jukic, I.; Boris, A.; Šušnjara, P.; Kolobaric, N.; Mihaljevic, Z.; Kralik, Z.; Kralik, G.; Koševic, M.; Galovic, O.; Stupin, A. (Applied Physiology, Nutrition, and Metabolism, 2025)
This randomized interventional study aimed to investigate the effect of carnosine-enriched chicken meat consumption on systemic endothelium-dependent and -independent micro- and macrovascular reactivity in thirty-five healthy competitive male athletes. Both forearm skin micro- and macrovascular endothelium-independent vasodilation were increased, and diastolic and mean arterial blood pressure (BP) were decreased in Carnosine group (n = 19) following the 3-week dietary protocol. Microvascular endothelium-dependent response (post-occlusion reactive hyperemia) was increased in the Carnosine group and significantly associated with decreased mean arterial BP level. Following dietary protocol, Controls (n = 16) had substantially higher urate (but still normal) levels than the Carnosine group. Carnosine supplementation in the form of functional food enhances endothelium-dependent and vascular smooth muscle-dependent vasodilation in peripheral micro- and microcirculation. Carnosine's effect on vascular endothelium could be attributed to its BP-lowering effect. Results suggest that carnosine has the potential to resist hyperuricemia in healthy individuals.